Development and research candies with increased biological value with protein-fat composite - Bochkarev, Sergiy; Cherevichna, Nataliya; Petik, Igor; Belinska, Anna; Varankina, Oleksandra; Zakhozhyi, Oleksandra; Ilina, Oleksandra; Shyrokova, Olena (Scientific Route, Estonia, 2017)
The composition of "truffle" cream candies enriched with polyunsaturated fatty acids of ω-3 group, sesamol and tocopherols antioxidants and plant proteins in the digestible form was developed. Cream candies contain a protein-fat composite based on flax, sesame and sunflower seeds. These products can be used both in everyday and in special nutrition of athletes, soldiers, heavy manual workers, children and young people. It was determined that the oxidative stability of the model creamy candy mass increased with the concentration of protein-fat composite in it. The positive effect of the plant supplement on taste, aroma and "mouth-feeling" sensation parameters was proved by the obtained profilogram of organoleptic quality control parameters of experimental samples of candy masses with different content of protein-fat composite. Thus, it was established that the protein-fat composite in the composition of sweets improved its organoleptic and physicochemical quality control parameters, and also increased shelf life. The development allows to increase the consumer evaluation of the quality of "truffle" cream candies and, accordingly, their competitiveness.
Keywords: candy mass; protein-fat composite; flax; sesame; sunflower seeds; oxidation; biological value